PROCESSING AND NUTRITIONAL VALUE OF BROILER LITTER AS A FEED FOR BUFFALO STEERS - S. M. Chaudhry; Z. Naseer (Journal of Animal and Plant Sciences, 2012)
Broiler litter was deep stacked in 1.21.21.2 m bins with 10%, 20% and 30% moisture for a period of 6 weeks. Following deep stacking all samples of broiler litter became negative for total, faecal CFU, Salmonella, Shigella and Proteus. Litter stacked with 30% moisture was used in a performance and digestibility trial. Twenty four buffalo steers were randomly assigned to four diets; i) basal diet (30% wheat straw, 29% wheat bran, 39% cotton seed cake and 1%mineral mix), ii) in the experimental diets cotton seed cake was replaced by deep stacked broiler litter to provide 13, 26, or 39% broiler litter in the total diet. Daily dry matter intakes were 8.76, 8.71, 8.27, and 7.95 kg/d for basal and waste containing diets, respectively. Dry matter intake and daily weight gain was lower (P<0.05) for the diets containing 39%broiler litter than basal and diets containing 13 and 26% broiler litter. The apparent digestibility values for DM and cell wall constituents were higher (P<0.05) for basal diet than broiler litter containing diets. Within litter containing diets higher digestibility values were for the diets containing 13 and 26% broiler litter than diet containing 39% broiler litter. Results from this study indicated deep-stacking is a safe method of eliminating pathogens from broiler litter and it can be used safely up to 26% in ruminant ration. However, it decreases the DM digestibility and DM intake when used at 39 %of the diet. Broiler litter has a potential to be used as a low-cost crude protein source for growing buffalo steers.
Keywords: Pathogenic organism; Broiler litter; deep stacking; Protein degradability; Buffalo steers